HERMENEUTIKA TEKS: SEBUAH WACANA DALAM METODE TAFSIR ALQURAN? - Ibrahim, Sulaiman (State Institute of Islamic Studies (IAIN) Palu, 2014)
Hermeneutics is a new phenomenon in the study of the Koran. There are still the pros and the cons among the flow and the groups in Islamic societies in accordabce with thw use of this method of interpretation. The pros group tends to claim that the existence of hermeneutic interpretation of feminism in the study of the Koran is a necessity. This is based on the statement that al-Qurâ€™Än á¹£Äliá¸¥ li kulli zamÄn wa makÄn. In the mean time, the couns group tends to state that hermeneutics is not proper to employ study orÂ to interpret the verses of the Koran. The reason is that the method is not part of a system of Islamic scholarship, but ratherÂ a method of biblical interpretation. This paper presents a discourse on the re-orientation of the interpretation of the Koran that involves existential through the interpretating actionsÂ relevant to the socio-cultural character ofÂ the community.Kata Kunci: hermeneutik, teks, Alquran, interpretasi, sosio-kultural